THE EFFECTIVENESS OF SCRABBLE, SYSTEM KEYBOARD AND WHITEBOARD LITERACY ON EARLY CHILDHOOD FINE MOTOR MOVEMENT ABILITY - Syaifuddin, Ahmad; Wijayanto, Adi (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The era of disruption is developing faster and faster so that teachers have difficulty choosing the right media in teaching early childhood reading. The purpose of the study was to determine the effect of the use of scrabbel media, system keyboards and whiteboards on fine motor movements in early childhood. The experiment was carried out during August as many as 8 times the research process with a 2x2 factorial design. The sample is the total student population of PELITA Hati Jeli and PAUD Cempak with experimental quasy techniques totaling 34 people using scrabble media, 32 through whiteboards, 31 with system keyboard media and 10 children from control class results. Variance analysis (ANAVA) and the Tukey Test were used to test hypotheses at significance α=0.05. The results showed that 1) perception of fine motor movements is high, scrabble literacy media is better than early childhood whiteboard literacy with results (Qo = 0,501 > Qt = 0,05), 2) perception of medium fine motor movements, tulia board literacy media is better than that of the early childhood system keyboard with results (Qo=0,133 > Qt = 0,05), 3) perception of low fine motor movements, the use of system keyboards for early childhood with results (Qo= 0,082 > Qt= 0,05), 4) overall in the total population showed that the average significance value was different i.e. (0,00 < 0,05). The conclusion of the study is that the media that have a significant effect based on the post-hoc test on the Tukey test are scrabble literacy 79,96, whiteboard literacy 70,97 and system keyboard literacy 57,81.